Warna-warni berbahaya: edukasi bahaya pewarna kimia pada jajanan anak sekolah di desa Karang Bunga - Lestari, Yulianita Pratiwi Indah; Miranti, Rizka Mulya; Riyadi, Ahmad Irfan; Raqiqah, Annisa; Hidayatullah, Aulia Fitriani; Silvana, Helen; Syawalia, Khaliza; Zannah, Miftahul (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Children are highly exposed to various snacks sold freely around schools, many of which may contain hazardous synthetic food dyes. These dyes can pose health risks, especially when consumed continuously without supervision. This community service aimed to increase students' awareness at SDN Karang Bunga about the dangers of synthetic food coloring in school snacks. The activity was conducted through counseling and education sessions on June 27, 2024. Methods included presentations, discussions, games, pretests and posttests, and questionnaire-based evaluations. The results showed increased knowledge based on the pretest and posttest scores and high satisfaction from teachers and students. This program is expected to build critical awareness among school-aged children in choosing safe food.